Clinical, Histopathological and Immunohistochemistry Evaluation of Reactive Cutaneous Histiocytosis in Canine in Western Amazonia - Bonfim, Elaine Rodrigues; Silva, Tamyres Izarelly Barbosa da; Melchior, Leonardo Augusto Kohara; Neves, Eduardo Cavalcante das; Souza, Soraia Figueiredo; Pelizzari, Charles; Malavazi, Patrícia Fernandes Nunes da Silva; Pacheco, Acácio Duarte (Acta Scientiae Veterinariae, 2020)
Background: Canine reactive cutaneous histiocytosis (RCH) is an immuneproliferative disease of skin histiocytes and is uncommon in occurrence. Its description in the literature is scarce and clinical studies are limited by the insufficient characterization of the patients' pathological findings. The objective of this report is to describe the clinical, histological and immunohistochemical findings of a case of canine reactive cutaneous histiocytosis in the state of Acre, Amazonia, Brazil. Case: It was attended at the Federal University of Acre, a 7-year-old male American pit bull terrier dog with nodular, allopecic and ulcerated lesions in the dorsal region of the ear, with purulent discharge and exacerbated painful tenderness. The animal was domiciled on the bank of the river Acre, municipality of Rio Branco, state of Acre, and suffered frequent parasitism by sandflies, especially in the head region. In the histopathological evaluation, hyperplastic cells were found, a large ulcerated area with the presence of fibrin and neutrophilic infiltrate in the epidermis. In the dermal layer, an inflammatory reaction pattern was identified, with the presence of fibrous connective tissue, dilated blood vessels and edema, however little defined. There was an intense presence of histiocytes with anisocytosis, in addition to neutrophils, plasma cells and lymphocytes in the perivascular and perianexal region. In immunohistochemistry, lysozyme and cell markers CD1a and Thy1 were detected, but negative result for E-cadherin and CD11d. The immunosuppressive therapy indicated with prednisolone, plus cephalexin for secondary infections and topical treatment, with clinical remission within two years. Discussion: Although the etiopathogenesis of RCH is poorly understood, it is believed that, in addition to the genetic factor, the disease is triggered by an antigenic trigger on the skin, such as dogs susceptible to ticks and sandflies. The accumulation of defense cells in the skin tissue, against the antigenic stimulus, generates primarily an inflammatory process too. Immune maladjustment of dendritic cells and leukocytes occurs in the walls of dermal vessels, as well as exacerbated recruitment of histiocytes, characteristics seen in cell morphology analyzes. In RCH, the proliferation of histiocytes between collagen fibers and the infiltration of round cells in the dermis are indicative of the disease, as evidenced in this report. The immunohistochemistry is the method of choice, which allows establishing the cellular origin that triggered the disease, although the characterization of a differentiation cluster is underused in veterinary medicine. In this context, we seek to identify histiocytes, which comprise the group of cells derived from CD34 +, macrophage precursors, dendritic and Langerhans cells of the epithelial tissue, which act as antigen presenters. It can be concluded that canine RCH is an uncommon disease resulting from an inflammatory process of the dermis with difficult to identify immune dysregulation. Differential diagnosis with systemic histiocytosis, cutaneous histiocytoma, histiocytic sarcoma, as well as leishmaniasis and mycobacteriosis, are fundamental through histopathological, serological and immunohistochemical evaluations, to establish the definitive diagnosis of the disease, as well as the prognosis, and to better direct the therapeutic approach of the case.